2018
DOI: 10.1007/s00253-018-9000-y
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous signal peptides-directing secretion of Streptomyces mobaraensis transglutaminase by Bacillus subtilis

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…Genes coding for Sec- or Tat-secreted proteins contain a 5′ sequence encoding the N-terminal signal peptide [ 44 ]. Remarkably, a given signal peptide can direct the secretion of different recombinant proteins [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Genes coding for Sec- or Tat-secreted proteins contain a 5′ sequence encoding the N-terminal signal peptide [ 44 ]. Remarkably, a given signal peptide can direct the secretion of different recombinant proteins [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is critical to the optimization of SP for the heterologous protein. S. mobaraensis TG was expressed in B. subtilis using SP wapA and SP amyQ [13]. Our study demonstrated that for S. ladakanum TG, the SP sacB and SP abnA were more suitable than SP wapA (Fig.…”
Section: Involvement Of the N-terminal Region Of Tg In Increasing Enzmentioning
confidence: 76%
“…In our previous study, active S. mobaraense TG was secreted by B. subtilis through the introduction of VMM into zymogen [14]. S. mobaraense TG was also secreted by B. subtilis through the Tat pathway [13]. These studies indicated that B. subtilis was a promising host for TG production.…”
Section: Sift Deskmentioning
confidence: 87%
See 1 more Smart Citation
“…The pro-peptide is essential for zymogen folding but must be posttranslationally cleaved to activate the zymogen [14]. Therefore, zymogen consisting of the propeptide and mature part of mTGase was normally expressed rst and the protease treatment was subsequently applied to remove the pro-peptide [15][16][17][18][19][20][21][22][23][24][25]. The protease treatment was either conducted in vitro [15-18, 20, 22, 23, 25] or accomplished through co-expression of the protease in vivo [19,21,24].…”
Section: Introductionmentioning
confidence: 99%